A case study for scientific research prior to conservation of marine metal artefacts. (June 2021) - van der Stok-Nienhuis, Janneke; Kuiper, Elisabeth; Beentjes, Tonny; Joosten, Ineke; van Eijck, Lambert; Zhou, Zhou; van Bommel, Maarten
Highlights: A rare 17th century brass box from a marine archaeological context was studied. Non-invasive analytical techniques were combined with complementary invasive ones. The extent of data gained prior to cleaning and conservation was demonstrated. Results aid stakeholders in making well-informed decisions. Abstract: A rare find of a high-status 17th century oval box, retrieved from a shipwreck, provided a unique opportunity to research the construction and finishing layers of an object that is untouched for 350 years. This case study was used to demonstrate the extent of data that can be gained from analytical techniques prior to conservation. The amalgam-gilt brass object was studied by optical and electron microscopy, X-radiography, micro-computed X-ray tomography, neutron tomography, X-ray fluorescence, X-ray diffraction, Rutherford backscattering spectrometry, proton-induced X-ray emission and gas chromatography. The results have led to a characterisation of the manufacturing methods used on the box and to a better understanding of the practicality of modern analytical methods and techniques in (maritime) archaeological research.